A COMPARATIVE ANALYSIS OF GAAP (USA) AND IFRS (EUROPE): EVALUATING THE NEED GLOBAL ACCOUNTING STANDARDS (GAS) - Khan, Md.Miraj Hossen (The journal of contemporary issues in business and government, 2025)
This study conducts a comparative evaluation of the Generally Accepted Accounting Principles (GAAP) in the United States and the International Financial Reporting Standards (IFRS) used in Europe between 2020 and 2023. The research examines key aspects such as implementation efficiency, financial disclosure transparency, fair value assessment, tax reporting, cybersecurity regulations, digital transformation, AI integration, audit quality, ESG adoption, political transparency, and GDP growth rates. The findings suggest that IFRS demonstrates greater uniformity and transparency, particularly in digitalization and ESG adoption, while GAAP remains stronger in audit reliability and regulatory enforcement. The study concludes that while IFRS is globally recognized for its flexibility, certain areas—such as cybersecurity disclosures and audit regulations— require improvements to align with GAAP’s structured framework. By integrating selected elements from both standards, a hybrid model could enhance the effectiveness of international financial reporting. The paper proposes that a Global Accounting Standard (GAS), combining the strengths of GAAP’s rule-based approach and IFRS’s principles-based flexibility, could serve as an optimal solution for addressing current limitations in global financial regulation.